Γαλλικά - Τα γεύματα της ημέρας - Ε'-ΣΤ' Δημοτικού Επ. 127 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: [♪ Μουσική Και σήμερα θα μιλήσουμε για το πρόγραμμα της ημέρας. Σε μια ημέρα, έχουμε 4 πρόγραμμα. Ξεκινάμε με το πρώτο πρόγραμμα, το πινι-δεγένειο. Είναι ένα πρόγραμμα πολύ σημαντικό για να έχεις ενέργεια και δυνατότητα για όλη η ημέρα. Το δεύτερο πρόγραμμα είναι το πινι-δεγένειο. Βρισκόμαστε από την εκκλησία, όπου ο πατέρας και η μητέρα βρισκόμαστε από το δουλειά τους και όλοι μαζί παίρνουμε το πινι-δεγένειο. Μερικές λεπτομέρειες, έχουμε το γούτε. Το γούτε είναι ένα πρόγραμμα λιγότερο. Μπορεί να είναι, για παράδειγμα, μια μπανάνα, ή γενικά μια πόμμα, ένα μπαρ από σεραίλ. Και στο τέλος του ημέρου, έχουμε το δινέμα. Όλη η οικογένεια μαζί, παίρνουμε το δινέμα. Ποια είναι οι στιγμές της ημέρας όπου παίρνουμε το πινι-δεγένειο? Το πρωί, παίρνουμε το πινι-δεγένειο. Λοιπόν, αυτό είναι το πρωί. Μετά, έχουμε το πρωί, παίρνουμε το πινι-δεγένειο. Η πραγματικότητα είναι ότι στην Ελλάδα παίρνουμε το πινι-δεγένειο πρωί, αλλά στην Ελλάδα θα είναι λίγο πλέον. Λοιπόν, μπορούμε να πούμε και την ώρα. Για να είμαστε πιο πραγματικοί, μπορούμε να πούμε και την ώρα. Την ώρα, την ώρα και πέμπτη, την ώρα και πέμπτη. Λοιπόν, το πρωί είναι η ώρα του γουτά. Και τέλος, έχουμε το δινέμα. Λοιπόν, βλέπουμε εδώ λίγο την πρώτη κάρτα. Τα πέντε φορές της ημέρας. Έχουμε πει το πινι-δεγένειο, το πινι-δεγένειο πλέον, το γουτά και τέλος το δινέμα. Και, φυσικά, θα προσθέσουμε τις στιγμές της ημέρας. Έχουμε πει, λοιπόν, ότι το πρωί είναι το πινι-δεγένειο, στο μέλλον, ή λίγο πλέον για τους Ελληνικούς, είναι το πινι-δεγένειο, το πρωί είναι το γουτά και, τέλος, το δινέμα είναι το ώρα. Λοιπόν, έχουμε μιλήσει για τις εξοπλήσεις και για τα στιγμές. Αλλά, ποιες είναι οι βέρβες που θα χρησιμοποιήσουμε για να μιλήσουμε για τις εξοπλήσεις της ημέρας? Θα κάνω λίγο το πινι-δεγένειο για να σας γράψω τις βέρβες, οι πιο σημαντικές βέρβες για να μιλήσουμε για τις εξοπλήσεις. Και, φυσικά, θα μπορείτε να καταλάβετε ότι το βέρβο που θα χρησιμοποιήσουμε είναι το βέρβο «μιλήσω». Το βέρβο «μιλήσω» είναι ένα βέρβο που τελειωθεί σε –er και έχουμε ήδη μιλήσει για βέρβους του πρώτου ομάδου, όπως το βέρβο «μιλήσω», το βέρβο «αμήσω», το βέρβο «μιλήσω». No problem, then, for the singular of the verb «manger», I use the necessary endings for the first person –ε. I eat, then. And for the second, you eat, with –es. Third person, he or she eats, with our ending –ε. And here, for the first person plural, we have we eat. And normally, here, after the letter –γ, I should write –ons, the ending. But it would be we miss. So, in order not to say we miss, I add here the letter –ε, be careful, and I mean we eat. I will not pronounce we eat, of course, it is not correct. I mean we eat directly. The following is easy. You eat, and the plural, he or she eats, with the ending –ent, for the third person plural. The verb «manger», then, is a very important verb. But when we are thirsty, we must also drink something. So, the second verb is the verb «drink». The verb «drink» is a verb of the third group. This verb will cause us some problems, but we will manage. So, I drink. You see, no –e at the end, but we have the letter –s. You drink, same thing. We have two times the same verb, I drink, you drink, he or she drinks, but it is with –t. Be careful, it is pronounced the same way, I drink, you drink, he drinks, but it is written with –t. The plural, a little more difficult. We drink. You see, the ending –ons is the same with us, with the verb of the first group. But the beginning is a little difficult. We drink and you drink, same thing. Same ending, but the beginning is –bu. The third person, a little more different. So, the ending –ent, but the beginning is «il boive». And be careful with the pronunciation. I drink, you drink, he drinks, we drink, you drink, they drink. With these two verbs, we can also use a third verb. It is the verb «prendre». The verb «manger», we said «je mange», «je bois» later, and «je prends» also. You can say «je prends une banane». So, I write you also the verb «prendre» and we will use it to talk about our meals. So, «je prends». You see, the ending with «s». You take, same thing, with «s», but «il» or «elle» of the singular, «prendre» with «des». Because I can't have «t» and «des» at the same time. So, I only keep the letter «des». We take, the endings are the same, –ons. You take, –ez. And finally, third person plural, «il» or «elle» «prenne». Be careful because there are two «n». «Il prenne», as if we accentuate that. I show you the three verbs here. You can see them and I erase the board. Hello! So, we have already said what are the four meals of the day. What are the moments of the day. We have also found the verbs that we will use. But you also have to be careful because there are different articles. What are the articles in French? So, the articles. We have the first type of articles, which are the definite articles. The definite articles. So, here I write it. That is «le, la, l',» and I use «l',» when the following word starts with a vowel. «A, E, I, O, U» and sometimes the letter «H». And then the plural. And I write you an example. «J'aime le chocolat». The verb «aimer». Or you can also use the verb «adorer». «J'adore le chocolat». Or the opposite, the negation «je n'aime pas le chocolat». But who doesn't like chocolate? And then «je déteste le chocolat». We can't say this sentence. And then the second type of articles are the definite articles. What are the definite articles? We have «en» for masculine. «une» for feminine. And the plural «des». And I can also give you an example. «J'ai une banane». And I give you here a second example. «Je mange une banane». Why did I give you this example? You will understand when I also explain the third type of articles. The partitive articles. What are the partitive articles? We have «du», «de la» for feminine. «De» and the apostrophe when the following word starts with a vowel. And then «des» from the plural. And my example here would be «je mange de la pizza». So what is the difference between the sentence «je mange une banane» and «je mange de la pizza»? You see «la banane». «Je mange d'habitude une banane complète». It's a third. Whereas for pizza, imagine that you have a big pizza and you are going to cut it and you are going to take a piece, two pieces, three pieces of this pizza. So it's not all pizza. That's why we use partitive articles. Because I take a part of the pizza. So that's for something I can eat entirely. And the other is when I take a part. So I show you the articles. You can see the definite, indefinite and partitive articles. And I make the table. And I continue with some examples. So let's see some examples. «Je bois l'eau» or «je bois de l'eau»? That's a question we ask ourselves. So we said verbs «manger», «boire» and «prendre» with the partitive. That's a category. So I can't say that and I keep «je bois de l'eau». The second example. We said that the verb «aimer», affirmation or negation, «j'aime» or «j'aime pas», the verb «adorer» and the verb «détester» that we have here, are conjugated with the definite articles. So «tu détestes le poisson». The third example. «Elle adore les» or «des croissants»? The same thing, the verb «adorer» is here, so with the definite articles. «Elle adore les croissants». Another example that is very easy. «Nous buvons» the verb «boire». I write «le» or «du lait». The verb «boire» is here with the partitive articles, so I mean «nous buvons du lait». «Vous mangez» that's the most difficult one. «Vous mangez de la» or «une banane»? «De la banane» or «une banane»? We said «c'est une banane complète», so «vous mangez une banane». And then the last example. «Il mange de la pizza» or «la pizza». The same thing because we said that it's a big pizza and we are going to take a part of it, so «il mange de la pizza». You can see now the sentences completed with the appropriate articles. «Je bois de l'eau», «tu déteste le poisson», «elle adore les croissants», «nous buvons du lait» and «vous mangez une banane», «il mange de la pizza». So we talked about meals, moments of the day, verbs that we can use, articles that we have to use and that's it. We can make sentences now. So I make the table and I start with the breakfast to make the complete sentence. So «le matin, au petit déjeuner, je mange» and there are several options. Most children prefer to eat cereals. So «je mange des céréales». It could also be bread with jam or a pie or bread with butter, strawberry jam. That's it. And what do you drink in the morning? So «au petit déjeuner, je mange et je bois du lait» or maybe orange juice. And I imagine that you can also say «mon père boit du café» or «mon mère boit du thé». That's it for breakfast. You saw the map, the complete sentence. «Le matin, au petit déjeuner, je mange des céréales», for example, «je bois du lait». We continue with the breakfast. So «à midi, au déjeuner, je mange» and there are also several options because you can say that you eat chicken, for example, fish, meat, and of course with that you will take I also take bread, I eat salad or frites that you like, I'm sure. And what do you drink? I just write «je bois de l'eau», the most important. «Boire de l'eau». Dad or mom can also drink wine, beer, whatever. And we continue with the lightest meal of the day, it's the snack. So I'll do it here a little bit. So «l'après-midi, au goûter, je prends des fruits d'habitude», right? You have to eat fruits. So «je prends des fruits» but you can be more precise by saying «je mange une banane, une pomme». There are also other fruits like orange or apricot, you can choose. There are also children who prefer to eat a cereal bar. And what do we drink? You can say «je bois du jus de fruits, du jus d'orange, du jus de fruits». And for the last meal of the day, we will see that it is finally the evening. So «le soir au dîner». This is also a lighter meal. So «le soir au dîner, vous pouvez prendre, vous pouvez manger un sandwich, peut-être du pain avec du fromage, un œuf aussi». Et qu'est-ce que vous buvez? If I write the sentence «je bois du lait ou je bois de l'eau», it depends on you. I will also show you the last card. «Le soir au dîner, je mange un sandwich, un œuf, du fromage, du pain et je bois de l'eau ou du lait». So you can very well talk about the meals of the day by saying at what time of the day, for example «le soir». This is the meal at the diner and you can explain what you eat and what you drink. Thank you very much, goodbye children and have a good day!